Diagnosos of proximal harmstring injuries - Schroeter, S.; Heiss, R.; Hammer, C. M.; Grim, C.; Engelhardt, M.; Hotfiel, T. (Sport-Orthopädie - Sport-Traumatologie, 2022)
Summary Injuries and overload to the hamstring muscles are frequently observed in recreational and high-performance athletes. The proximal hamstring muscle complex is in a highly vulnerable region that is likely to sustain injury in several disciplines. Proximal hamstring injuries (PHI) are responsible for a substantial loss of training and competition days. A precise and targeted diagnostic approach is essential to provide a correct assessment of injury severity. In general, a careful anamnesis and thorough clinical examination with inspection, palpation, and functional testing provide substantial information about the extent and severity of injury. Imaging of muscle tissue is essential to confirm precise diagnosis for providing further assessment of the degree of damage or differential diagnosis. Understanding the specific tasks in the diagnosis of PHI requires knowledge of functional anatomy, injury, and pathophysiological mechanisms as well as examination and imaging techniques. The present work provides a structured overview of the diagnostic work-up of PHI, emphasizing structured examination and imaging techniques to enable reliable diagnosis and rapid treatment decisions.